Coronavirus Disease 2019 and Gastrointestinal Involvement: A Systematic Review - Monica, Moryella; Kurniawan, Andree (Fakultas Kedokteran Universitas Pelita Harapan, 2020)
Introduction: The World Health Organization (WHO) announced the Coronavirus 2019 (COVID-19) as a Public Health Emergency of International Concern (PHEIC) toward the end of January 2020. There is still limited evidence to explain the gastrointestinal involvement in COVID-19. In this study, we aimed to further investigate current evidence describing the gastrointestinal involvement in COVID-19 patients.Methods: This systematic review has been registered in PROSPERO (CRD42020181584). A systematic search of literature for observational and randomized controlled trial was conducted in PubMed, PubMed central, and Google Scholar through April 16, 2020. Two reviewers independently searched and selected. The risk of bias was evaluated using the Newcastle-Ottawa Quality assessment tool. Results: A total of 1,480 articles were screened from which 12 articles with 5584 subjects were selected. SARS-CoV-2 can invade human body by binding to angiotensin converting enzyme 2 (ACE-2) receptor which also located to small intestinal epithelial cells, crypt cells and colon. The virus itself may cause disorders of the intestinal flora. The diagnosis should be based on a set of symptoms diarrhoea, nausea, vomiting, abdominal discomfort or pain, combined with positivity of faecal PCR test. Treatment of COVID-19 mainly is supportive care. The probiotic may modulate the gut microbiota to alter the gastrointestinal symptoms and reduced enteritis, ventilator associated pneumonia, and reverse certain side effect of antibiotics.Conclusion: Our synthesis of literature showed that there was no good evidence yet in overall area of gastrointestinal manifestations in COVID-19. Future research is needed to explore all areas, especially in mechanism and treatments